Detecting the effectiveness of two tools for detecting the talented from their teachers' points of view (Journal of the College of Education for Women, 2019)
Education specialists have differed about determining the best ways to detect thetalented. Since the appearance of the mental and psychological measurement movement, somescholars adopted intelligence ratios as a criterion to identify the talented and others went torely on the degree of academic achievement. Each of these two methods has its own flaws andmistakes and a large number of talented children were victims of these two methods.Therefore the need to use other scales for the purpose of detection of talented childrenappeared because they provide valuable information which may not be obtained easilythrough objective tests and these scales are derived from consecutive studies of gifted andtalented children , or from the conduct of the life of the talented people and genius who lefttheir clear imprint in the history of human civilization and these scales are filled by teachersor counselors staying stick to the talented children in school and some of them filled byrelatives and colleagues.Therefore, the researcher has adopted two scales and makes a comparison betweenthem by extracting the psychometric properties in order to identify which one is better atdetecting talented.The first measure is of (Renzulli, 1979) which estimates the behavioral traits ofgifted students in the areas of stimulus, learning, and creativity.The second measure is of (Steinberg, 2010) in which he confirms on the threeabilities: analytical ability, creative ability, and the practical ability. He stressed on thebalance between these three abilities for the emergence of the talent of the child.In order to achieve the goal of this research, the researcher has applied the scale on asample of gifted students consisted of (63) students into three schools for gifted students inBaghdad, Najaf, and Basra. Twelve teachers were selected from schools who have teachingexperience of more than three years and are adjacent to the talented student monitoring his/herbehaviors. The researcher has reached, after extracting the psychometric characteristics ofeach of the two scales, that both have high stability and high structure validity.The researcher has recommended the adoption of the two scales as a basis fordetecting the talented by their teachers with the aim of sending those talented students toprivate schools special for gifted students, or if these students are found in ordinary schools,special classes and programs for the development and refinement of their talent are allocatedto them and make the utmost benefit of it. The researcher has suggested doing more on themethods of the detection of talented and applied them early on the children before it is toolate.